Towards a Child-Friendly City in East Aceh through Collaborative Governance and Local Challenges - Mukhlis Mukhlis; Muammar Muammar; Fitri Maghfirah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The development of Child-Friendly Cities (CFC) is a strategic initiative to ensure the fulfillment of children's rights in urban governance. Specific Background: Despite national efforts, until 2023, no city or regency in Indonesia has achieved the